Structure–activity relationship of 2,2-dimethyl-2H-chromene based arylsulfonamide analogs of 3,4-dimethoxy-N-[(2,2-dimethyl-2H-chromen-6-yl)methyl]-N-phenylbenzenesulfonamide, a novel small molecule hypoxia inducible factor-1 (HIF-1) pathway inhibitor and anti-cancer agent - Mun, Jiyoung (Bioorg Med Chem, 2012)
We have discovered that 3,4-dimethoxy-N-[(2,2-dimethyl-2H-chromen-6-yl)methyl]-N-phenylbenzenesulfonamide, a novel small molecule HIF-1 pathway inhibitor, can antagonize tumor growth in animal models of cancer, but the treatment necessitates its delivery in a formulation, due to poor water solubility (<15 μg/mL; pH 7.4), evidencing that the chemotype needs further exploration of its amenability to additional chemical modifications for ultimate optimization of function and pharmacology. As a first step towards this goal we investigated the structure–activity relationships of 15 lipophilic 2, 2-dimethyl-2H-chromene based arylsulfonamide analogs of 3,4-dimethoxy-N-[(2,2-dimethyl-2H-chromen-6-yl)methyl]-N-phenylbenzenesulfonamide to find out strategies of modification. A 3,4-dimethoxybenzenesulfonyl group in region 1 showed the strongest inhibition among five arylsulfonyl groups tested. The presence of propan-2-amine in region 2 conferred the strongest inhibitory effect of the compound on HIF-1 activated transcription in a reporter assay. These findings are important as they help define the structural motifs where the 3,4-dimethoxy-N-[(2,2-dimethyl-2H-chromen-6-yl)methyl]-N-phenylbenzenesulfonamide can be chemically modified to improve its pharmacological properties towards development as a cancer therapeutic.